Implications of the state assistance program in the province of Quebec: the case of lamb production - Sedghy, bahareh; Tamini, Lota Dabio; Lambert, Remy (European Journal of Applied Sciences, 2022)
This study investigated the impact of the Farm Income Stabilization Insurance (ASRA) on the adoption of price risk management strategies by lamb producers in the province of Quebec. This study employed a Generalized Autoregressive Conditional Heteroskedasticity (GARCH) process to model price risks. The results indicated that the application of the Farm Income Stabilization Insurance in Quebec generates crowding-out effects on price risk management strategies, which decreases the efficiency of this program. On the other hand, the product-specific nature of ASRA leads to some challenges such as a modification in the revenue distribution across the farm, increased production, increased indebtedness of farmers and increased financial burden on governments’ shoulders. Finally, the results revealed an asymmetric impact of positive and negative shocks on the production decision of lamb producers. This asymmetric impact of negative and positive shocks generated by ASRA results in an increasing risk-aversion of producers over the periods of decreased prices and a decreasing risk aversion over the periods of increased prices.